Farmers Access, Adoption Behaviour and Constraints Analysis in Improved Technology Dissemination: A Case Study on System of Rice Intensification in Bihar - Handral, Ankhila R.; Sahoo, Alok Kumar; Sethy, Jyoti Prakash (Indian Journal of Extension Education, 2017)
System of Rice Intensification (SRI) is an environment well disposed and novel strategy of rice cultivation which  incorporates utilization of less seed, less water and fewer chemicals to obtain higher yield and profitability. A study was  undertaken in Bihar to assess the extent of adoption of SRI and its determinants and constraints using primary data  collected for the Agricultural Year 2013-14. Tabular analysis, Tobit regression, Garrett's ranking were employed.  Adoption index showed transplanting early seedling having highest weightage and poor adoption in all SRI practices.  Tobit analysis indicated that access to extension and number of training attended has significant influences on adoption of  SRI package of practices. Non- availability of skilled labour was found to be the major constraint in adoption of SRI  method. To realize the inclusive and full benefit of SRI technology, the efforts should be directed to enhance the adoption  of recommended practices of SRI by all the stakeholders, demonstration of SRI cultivation on farmers' fields, training to  farm labourers, standardize the SRI practices and mechanization of SRI operations.
Keywords: SRI; tobit analysis; Garrets Ranking; Adoption Index; Adoption Behaviour